An overview of educational inequality in India: The role of social and demographic factors - Garg, Mausam Kumar; Chowdhury, Poulomi; SK, Md Illias Kanchan (Frontiers in Education, 2022)
Objective To assess the change in the level of educational inequality and the contribution of social factors and demographic factors. Data source Three rounds of National Sample Survey viz. 64th (2007–2008), 71st (2014), and 75th (2017-2018) have been used. Methods Education Gini is used to study the extent of educational inequality over the time period. Decomposition method is used for "within-group" and “between group” inequality. Tobit regression model is utilized to study factors influencing average years of schooling (AYS). Finally, regression-based Shapley decomposition method is used to identify factors contributing in educational inequality. Results The level of AYS has improved over the period and reached to 7.7 years in 2018. Further, the level of educational inequality gone down between 2007 and 2018, but the Gini indices are still concentrated around 38%. Decomposition of the Gini and Shapley regression approach indicates that the within-group component and rural-urban division contribute the most to educational inequality. Tobit model signifies that digital exposure, household occupation, wealth quintile, and household size play a key role in determining educational attainment. Conclusion The paper underscores the improvement of education in rural areas by focusing on school infrastructure, e-learning, educational quality, and parent involvement.